Winter Annual Grass Control in Winter Wheat - D. E. Peterson; C. Thompson; C. L. Minihan (Kansas Agricultural Experiment Station Research Reports, 2017)
Winter annual grasses can be difficult to manage in winter wheat. A field experiment was established near Manhattan, KS, in 2016 to evaluate various preemergence and postemergence herbicide treatments for control of downy brome, cheat, and feral rye. Most treatments were less effective for control of downy brome than cheat. Preemergence and fall postemergence treatments provided better downy brome control than spring postemergence treatments. All herbicide treatments evaluated provided excellent control of cheat, but postemergence treatments were slightly better than preemergence treatments. The only herbicide to control rye was Beyond, which provided better control when applied fall postemergence than spring postemergence.
Keywords: Wheat; downy brome; cheat; rye